Identification of Ferroptosis-Associated Genes in Prostate Cancer by Bioinformatics Analysis - Wo, Qijun; Liu, Zhenghong; Hu, Linyi (Frontiers in Genetics, 2022)
Background: In order to reveal the functions of ferroptosis in prostate cancer (PCa), ferroptosis potential index (FPI) was built. This study researched the influence of ferroptosis on gene mutations, various cellular signaling pathways, biochemical recurrence (BCR), and drug resistance in both FPI-high and FPI-low groups. Methods: RNA-seq, somatic mutation data and clinical data were obtained from The Cancer Genome Atlas (TCGA). FPI values were calculated. All samples were divided into FPI-high and FPI-low groups. The BCR-free survival rate, tumor mutation burden (TMB) value, cellular signaling pathway, differentially expressed genes (DEGs) and drug resistance in the two FPI groups were identified. Human PCa cells LNCaP were treated with ferroptosis inducer erastin or inhibitor ferrostatin-1. The expression of hub genes was detected by qRT-PCR and western blot. Results: High FPI level was significantly related to poor BCR-free survival. Also, higher TMB value was found in the FPI-high group, and FPI was shown to be associated with gene mutations. Then, genes in both groups were revealed to be enriched in different pathways. 310 DEGs were identified to be involved in muscle system processes and neuroactive ligand-receptor interactions. 101 genes were found to be related to BCR-free survival, and protein-protein interaction (PPI) network was constructed. Two sub-modules were identified by MCODE, and 8 hub genes were screened out, among which SYT4 had higher expression levels and poorer BCR-free survival in the FPI-high group, while the remaining hub genes had lower expression levels and poorer BCR-free survival. Drug sensitivity was revealed to be different in the two groups by study on the IC50 data of different molecules and ferroptosis regulator gene (FRG) expressions. Finally, erastin increased the expression of SYT4 in LNCaP, and decreased the expression of the other 4 genes (ACTC1, ACTA1, ACTN2, and MYH6) while ferrostatin-1 led to the opposite results. The molecular experimental results were consistent with those of bioinformatics analysis, except TNNI1, TNNC2 and NRAP. Conclusions: The current research depicted the ferroptosis level and FRGs in PCa. Ferroptosis was related to TMB value, BCR-free survival and drug resistance. This study will be beneficial to further researches on ferroptosis-related molecular mechanisms.